Development of The Character Education Evaluation Model In Schools - Adi Rosadi; Aan Hasanah; Bambang Samsul Arifin (Universitas Muhammadiyah Enrekang, 2023)
The research aims to examine the development of a character education evaluation model in schools and madrasahs. This research adopts a qualitative descriptive method using literature review. The study concludes that character education focuses on the affective and psychomotor domains, which are evaluated through questionnaires, inventories, portfolios, and observations. The implementation involves intracurricular, extracurricular, and school cultural activities. The evaluation methods include observation, self-assessment, teacher observation, tests, quizzes, discussions, and reflections. The evaluation criteria encompass caring, cooperation, commitment, courage, change, relationships, coherence, consensus, communication, culture, and criticality. Character education holds significant meaning as it shapes positive habits in cognitive, affective, and behavioral domains. The evaluation also involves assessing the performance of educators, educational staff, and students